Developing business strategy of warbis prama in food and fashion industry - Aulia, Hilmi; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2018)
Abstract. Warbis Prama is a Business Development Services company. Warbis Prama is part of the Ministry of Cooperation from 2002 until 2014. In 2014 they got independent as they see the opportunities from internal and external factors. There is 57.895.721 number of the total Indonesia SME's where all most the total came from all of SME industry. Those amount of SME's are the best opportunity for Warbis Prama to expand their business. Furthermore, Warbis Prama had a great partnership to serve and develop the SME as they are have been part of the ministry of cooperation before. They had so many experiences with Ministry of Cooperation. So Warbis prama top management level are eligible to run the business.  Furthermore, they had many projects with Ministry of SME. Those experience determine Warbis Prama core value. The final result shows Warbis Prama is eligible to be independent and give input to the Warbis Prama based on the research and business strategy method. Secondly, Warbis Prama can run the business through a business strategy that fit to them in the future. The third,  Explanation about Warbis Prama should do in the future with the proper implementation plan. So, Warbis Prama can develop their business and achieve sustainability advantage in the future